INTERAKSIONISME SIMBOLIK PADA KOMUNITAS CINEMA APPRECIATOR MAKASSAR DI KOTA MAKASSAR - Emanuel Omedetho Jermias; Abdul Rahman (Pusat Riset dan Inovasi Nasional, 2022)
ABSTRACT Cinema Appreciator Makassar is a community that was formed because of the common interest in film appreciation. The activities that are usually carried out by the community are conducting film screenings and actively participating in creative spaces or activities in Makassar City. The context of cinema in the Makasar Cinema Appreciator room is a film that is not screened in theaters and tends to have educative themes. This community is characterized as alternative cinema, film and photography, as well as literacy and creativity. In maintaining its existence, Cinema Appreciator Makassar seeks to carry out community activities in a sustainable manner. Cinema Appreciator Makassar is a small space that represents the face of the city's ever-evolving lifestyle. Members generally use this space as their way of having entertainment, fun, and experiences. The lifestyle of urban communities is always transformed based on references and perceptions. Generally they assume that the lifestyle they do is a necessity to always share and learn.